2021
DOI: 10.1161/strokeaha.120.031800
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Core Overestimation on Computed Tomography Perfusion

Abstract: Background and Purpose: Different studies have pointed that CT perfusion (CTP) could overestimate ischemic core in early time window. We aim to evaluate the influence of time and collateral status on ischemic core overestimation. Methods: Retrospective single-center study including patients with anterior circulation large-vessel stroke that achieved reperfusion after endovascular treatment. Ischemic core and collateral status were automatically estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(90 citation statements)
references
References 43 publications
(68 reference statements)
4
85
1
Order By: Relevance
“…Our report and other studies show that a favourable collateral profile is often concordant with that of perfusion. Moreover, there is evidence to suggest that perfusion imaging can overestimate the extent of irreversibly damaged brain tissue 31. Results from ongoing randomised trials that select late-window patients for EVT versus medical treatment using CT/CTA may provide further evidence on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Our report and other studies show that a favourable collateral profile is often concordant with that of perfusion. Moreover, there is evidence to suggest that perfusion imaging can overestimate the extent of irreversibly damaged brain tissue 31. Results from ongoing randomised trials that select late-window patients for EVT versus medical treatment using CT/CTA may provide further evidence on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are compatible with prior studies that suggested that ischemic core thresholds may be time-dependent [22][23][24] and stricter core thresholds should be used for patients who received perfusion imaging very early after symptom onset. 25 Ischemic core overestimation is a potential concern that has been controversial in the stroke community, with recent articles 14,21,26 suggesting that patients may be excluded from receiving EVT based on CTP overestimation of irreversible injury. The purpose of this study was to evaluate whether infarct core overestimation is frequent with the currently established rCBF <30% threshold, the effect of time from LKW and time from imaging to successful reperfusion on the incidence of potential overestimation, and whether the core overestimation can be eliminated with a more stringent rCBF <20% threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Significant underestimation of infarct volume was defined as the follow-up infarct volume being at least 25 mL larger than estimated ischemic core volume on baseline CTP, 19,20 whereas core overestimation was defined as ischemic core volume at baseline being ≥10 mL larger than infarct volume on follow-up DWI. 14,21 The rest were defined as adequate estimation (core corresponding to DWI infarct).…”
Section: Methodsmentioning
confidence: 99%
“…The different definition of study endpoints (ENI versus mRS at day 90) might be one explanation. Another reason might be ischemic core overestimation on CTP, particularly in patients in earlier time windows and those with rapid reperfusion [33][34][35]. Due to potential presence of ghost infarct core on CTP, caution must be applied in decision-making for endovascular therapy in patients presenting with early time window within 3 h [36].…”
Section: Discussionmentioning
confidence: 99%